Insights into the Underlying Mechanism of the Piriformospora indica-Enhanced Drought Tolerance in Blueberry - Yongyan Zhang; Pengyan Qu; Junke Zhang; Ruide Li; Rui Liu; Chunzhen Cheng (Horticulturae)
Piriformospora/Serendipita indica has been frequently proved to play a crucial role in enhancing plant adaptation to environmental stresses. However, its influence on blueberry (Vaccinium corymbosum) drought tolerance has not yet been studied. Here, we reported that P. indica colonization can significantly enhance the drought tolerance of blueberry. Physio-biochemical parameter determination results showed that, compared to non-colonized controls (CK), P. indica-colonized (PI) plants exhibited higher leaf chlorophyll and carotenoids contents, photosynthetic capacity, biomass and root antioxidant enzyme activities (superoxide dismutase and catalase), while also exhibiting lower root malondialdehyde content under drought stress (DS). To explore the underlying mechanism, comparative root transcriptome analysis of well-watered (WW) and DS-treated CK and PI blueberry plants was conducted. In total, we identified 14,587 differentially expressed genes (DEGs) across CK-WW vs. CK-DS, PI-WW vs. PI-DS, CK-WW vs. PI-WW and CK-DS vs. PI-DS comparisons. Under DS, stress-, metabolism- and regulation-related DEGs were overwhelmingly upregulated in PI, while being downregulated in CK. Weighted gene co-expression network analysis categorized DEGs into four modules. Of them, the MEblack module was significantly correlated with the PI-DS group, with DEGs enriched in the cell wall macromolecule catabolic process, carbohydrate metabolic process, phenylpropanoid biosynthesis, and so on. Several defense-related genes, including four thaumatin family proteins, were identified as hub genes of this module. DEGs in the MEblue module were expressed at the highest level in CK-DS, followed by in PI-DS. Hub genes of the MEblue module included DEG-encoding lipid transfer protein, abscisic stress ripening protein, and so on. This study demonstrates that P. indica enhances blueberry drought tolerance by enhancing antioxidant ability and mediating the expression of genes related to stress, carbohydrate and secondary metabolism, and cell wall metabolism.